A Imagem como documento para radiologia forense: um olhar da Biblioteconomia - SOUSA, Elivane Nazaré Soares de (2023)
It approaches the radiological image in its legal value for Forensic Radiology. The discussion assumes an interdisciplinary character, consisting of a theoretical work based on bibliographic research. The paper discusses themes such as Documentation, Document, Information Science, Information, Forensic Medicine, Forensic Radiology, and radiological image, seeking to understand the three dimensions of the image in its informative potential, namely: as a represented being/object; the professional specialized in the production of the radiological image; and the technology used in the production of the image. As a document that represents the materiality of a crime (evidence), the radiological image serves as support to a number of professionals such as coroners, delegates, lawyers, judges, journalists and others interested in the ascertainment of a crime. It concludes that there is a gap in the field of Librarianship and Information Science regarding the informational potential of the image in the field of Medicine, and more specifically in Forensic Medicine. Therefore, more studies are needed in this area, which dialogs directly with the judicial sphere, paving the way for deeper analyses of image information.